Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the inequality [tex]\(-4(8 - 3x) \geq 6x - 8\)[/tex], let's follow a step-by-step process:
1. Distribute the [tex]\(-4\)[/tex] on the left side of the inequality:
[tex]\[ -4(8 - 3x) \geq 6x - 8 \][/tex]
This gives us:
[tex]\[ -4 \cdot 8 + (-4) \cdot (-3x) \geq 6x - 8 \][/tex]
Simplifying further:
[tex]\[ -32 + 12x \geq 6x - 8 \][/tex]
2. Combine like terms:
To simplify, let's move all the terms involving [tex]\(x\)[/tex] to one side and constant terms to the other side. Subtract [tex]\(6x\)[/tex] from both sides:
[tex]\[ -32 + 12x - 6x \geq -8 \][/tex]
Simplifying, we get:
[tex]\[ -32 + 6x \geq -8 \][/tex]
3. Isolate the [tex]\(x\)[/tex] term:
Now, add 32 to both sides to isolate the [tex]\(x\)[/tex] term:
[tex]\[ -32 + 6x + 32 \geq -8 + 32 \][/tex]
Simplifying, we have:
[tex]\[ 6x \geq 24 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
Finally, divide both sides by 6:
[tex]\[ x \geq \frac{24}{6} \][/tex]
Which simplifies to:
[tex]\[ x \geq 4 \][/tex]
So, the solution to the inequality [tex]\(-4(8 - 3x) \geq 6x - 8\)[/tex] is:
[tex]\[ x \geq 4 \][/tex]
The correct answer is:
[tex]\[ x \geq 4 \][/tex]
1. Distribute the [tex]\(-4\)[/tex] on the left side of the inequality:
[tex]\[ -4(8 - 3x) \geq 6x - 8 \][/tex]
This gives us:
[tex]\[ -4 \cdot 8 + (-4) \cdot (-3x) \geq 6x - 8 \][/tex]
Simplifying further:
[tex]\[ -32 + 12x \geq 6x - 8 \][/tex]
2. Combine like terms:
To simplify, let's move all the terms involving [tex]\(x\)[/tex] to one side and constant terms to the other side. Subtract [tex]\(6x\)[/tex] from both sides:
[tex]\[ -32 + 12x - 6x \geq -8 \][/tex]
Simplifying, we get:
[tex]\[ -32 + 6x \geq -8 \][/tex]
3. Isolate the [tex]\(x\)[/tex] term:
Now, add 32 to both sides to isolate the [tex]\(x\)[/tex] term:
[tex]\[ -32 + 6x + 32 \geq -8 + 32 \][/tex]
Simplifying, we have:
[tex]\[ 6x \geq 24 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
Finally, divide both sides by 6:
[tex]\[ x \geq \frac{24}{6} \][/tex]
Which simplifies to:
[tex]\[ x \geq 4 \][/tex]
So, the solution to the inequality [tex]\(-4(8 - 3x) \geq 6x - 8\)[/tex] is:
[tex]\[ x \geq 4 \][/tex]
The correct answer is:
[tex]\[ x \geq 4 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.